The effect of porang (Amorphophallus muelleri) extract on renal histopathological changes - Evan Ricardo; Bernadette Dian Novita; Niluh Suwasanti; Jovan Amadeo Muliyanto; I Gusti Agung Putu Diah Meliana Dewi; Ferdinand Jaya (Wolters Kluwer Medknow Publications, 2024)
Diabetes mellitus is a chronic condition defined by elevated blood sugar levels (hyperglycemia). This condition can lead to complications such as nephropathy, which is histologically shown with glomerulosclerosis. Glucomannan, a component of Amorphophallus muelleri, offers numerous health benefits, but its direct therapeutic effect on glomeruli remains uncertain. Male Wistar rats which were taken with random sampling (n = 30) were distributed into six distinct groups. All groups, excluding Group N, received 125 mg/kg BW single intraperitoneal dose of alloxan. Group N received a single dose of PBS 125 mg/kg BW. After 7 days, Group K + was induced with acarbose at a dose of 50 mg/70 kg BW (adjusted using a factor of 0.018) orally per day. Groups N and K − induced with 1% CMC Na at 0.2 mL/0.1 kg orally per day. While Group P1, P2, and P3 were orally given A. muelleri ethanolic extract orally per day at a dose of 100, 200, and 400 mg/kg BW. The following 50 days of treatment, the Wistar rats were euthanized, and their kidney was preserved for histological slides that were stained with hematoxylin and eosin. The oral administration of A. muelleri ethanolic extract in alloxan-induced diabetic rats led to a significant decrease in the average of glomerulosclerosis instances when compared to the K − group. The most effective dose was observed at 400 mg/kg BW per day. A. muelleri administration leads to a reduction in glomerulosclerosis occurrences, suggesting its potential as a therapeutic approach for reducing complications probability linked to hyperglycemia.